Cancer wars: natural products strike back - Basmadjian, Christine; Zhao, Qian; Bentouhami, Embarek; Djehal, Amel; Nebigil, Canan G.; Johnson, Roger A.; Serova, Maria; de Gramont, Armand; Faivre, Sandrine; Raymond, Eric; Désaubry, Laurent G. (Frontiers in Chemistry, 2014)
Natural products have historically been a mainstay source of anticancer drugs, but in the 90’s they fell out of favor in pharmaceutical companies with the emergence of targeted therapies, which rely on antibodies or small synthetic molecules identified by high throughput screening. Although targeted therapies greatly improved the treatment of a few cancers, the benefit has remained disappointing for many sol¬¬id tumors, which revitalized the interest in natural products. With the approval of rapamycin in 2007, twelve novel natural product derivatives have been brought to market. The present review describes the discovery and development of these new anticancer drugs and highlights the peculiarities of natural product and new trends in this exciting field of drug discovery.